2021
DOI: 10.1016/j.jtauto.2021.100102
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib treatment for refractory nontuberculous mycobacterial infection in the setting of interferon gamma autoantibodies

Abstract: Interferon-γ autoantibodies increase the risk of disseminated nontuberculous mycobacterial infections. Addition of rituximab to antibiotics accelerates and improves outcomes, but refractory infections can occur due to persistent production of autoantibodies. We combined bortezomib with rituximab to reduce autoantibodies leading to clinical and radiographic improvement in infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…One patient used RTX before the diagnosis of AOID due to suspected IgG4RD [ 17 ], and another patient used RTX due to the diagnosis of diffuse large B cell lymphoma after 2 years [ 18 ]. The commonly used protocols were 375 mg/m 2 weekly to monthly [ 19 21 ] or 1 g monthly [ 22 24 ]. The median treatment times for the patients with RTX and without RTX were 22 months (1.5 ~ 156 months) and 16 months (0.5 ~ 92 months), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient used RTX before the diagnosis of AOID due to suspected IgG4RD [ 17 ], and another patient used RTX due to the diagnosis of diffuse large B cell lymphoma after 2 years [ 18 ]. The commonly used protocols were 375 mg/m 2 weekly to monthly [ 19 21 ] or 1 g monthly [ 22 24 ]. The median treatment times for the patients with RTX and without RTX were 22 months (1.5 ~ 156 months) and 16 months (0.5 ~ 92 months), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Four patients had only partial remission [ 14 , 21 , 25 ], and another three patients had progressive infection even after RTX treatment [ 21 , 26 ]. Two patients failed RTX but achieved disease control with bortezomib [ 22 ] or daratumumab [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, combining BTZ with an immunosuppressive agent that targets plasma cell precursors, such as rituximab, is likely necessary to prevent the generation of new plasma cells. A previously published case study reported successful reduction of anti-IFN-γ-auto-Abs and improved IFN-γ-induced STAT-1 phosphorylation after BTZ administration in patients with refractory infections after rituximab treatment, which resulted in a better clinical and radiological outcome [ 34 ]. In addition, daratumumab, which is a novel anti-CD38 monoclonal antibody, was also reported to decrease anti-IFN-γ-auto-Abs after rituximab combined with BTZ [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, healthcare providers should consider turning to immunosuppressive drugs with other targets rather than extending the use of rituximab and cyclophosphamide. Recent case reports have identified other immunotherapies, such as daratumumab (a monoclonal antibody targeting CD38) ( 24 ), bortezomib (a proteosome inhibitor) ( 23 ), and adalimumab (a tumor necrosis factor inhibitor) ( 31 ), which can improve the prognosis of patients with a poor response to treatment with rituximab and cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%